Delirium detection in hospitalized adults: the performance of the 4 'A's Test and the modified Confusion Assessment Method for the Emergency Department. A comparison study - Muser, Olga (2023)
During the study period, 211 patients were hospitalized on the six wards, of whom 116 were included in the study. A total of 95 patients were excluded due to, for instance, refusal to participate (n = 29), admission after assessment (n = 22) or absence of patients (n = 19) (Fig. 2).The median age of patients was 73.0 years (interquartile Q1 56.3, Q3 83.0) and 49 (42.2%) of the patients were women. Pre-existing dementia was present in 11 (9.5%) patients. A total of 8 out of 116 patients (6.9%) had delirium according to the gold standard, the mCAM-ED, and 16 (13.8%) had delirium according to the 4AT. Subgroup analysis of patients with delirium and patients without delirium showed no statistically significant difference in the development of delirium in respect to age (U = −1.799, p = 0.072), sex (p = 1.000) or pre-existing dementia (p = 0.167) (Table 2). There was a wide range of main diagnoses and heterogeneity among the patients (Additional file 1: Table 5), and two-thirds of them were hospitalized on medical wards